Processos participativos na produção audiovisual: o caso do vídeo mulheres mangabeiras, de Sergipe - Silva, Ana Lúcia Assunção da (2014)
The research aims at investigate the production process of the video |Mulheres Mangabeiras| (mangaba pickers women) in order to verify whether and how there was use of participatory methods. This is a qualitative and descriptive research, based on methodological procedures such as literature review and data collection through open interviews. Data analysis layed upon extracts from women speeches, which contains indicators about their involvement in ex tractive production, as well as their perceptions about public visibility and empowerment offered by the video production. The results show that mangabeiras were protagonists in a kind of participatory communication, pointing to the potential of participatory processes in audiovisual production as a reaffirmation of individual and collective identities, which also brings out critical mind, dialogue promotion and a conflict management tool.